Optimizing Power-to-Gas Technology for Efficient Renewable Energy Storage and Integration in Germany: a Review - Oloruntoba , Emmanuel Olalekan; Oladosu, Olayinka Amos; Samuel, Ayedogbon Ayodeji; Bode, Agunbiade Michael; James, Adedayo (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study explores the integration of renewable energy sources into the German power grid, with a specific focus on the application of Power-to-Gas (PtG) technology as a solution for energy storage and optimization. Amidst the growing penetration of renewables, characterized by their intermittent nature, the challenge of maintaining a stable and reliable energy supply becomes paramount. This research delves into the use of Polymer Electrolyte Membrane (PEM) electrolysis for hydrogen storage and biological methanation within the PtG process chain, aiming to enhance the efficiency of methane production and the operational performance of trickle-bed reactors. By developing an economically viable approach for PtG technology and suggesting future business models, this work contributes to the identification of the most suitable electrolysis technology for sector coupling and grid integration. The findings indicate that PtG not only offers a promising pathway for the sustainable integration of renewable energies but also underlines the need for novel, application-oriented storage solutions and the optimization of system components for better market penetration and efficiency. This research underscores the pivotal role of PtG technology in bridging the gap between renewable energy production and the existing energy infrastructure, paving the way for a more sustainable and resilient energy system in Germany.